Pe Peningkatan Pengetahuan dan Sikap Keluarga dalam Memilah Sampah B3 Rumah Tangga Melalui Pendampingan - Ruhmawati, Tati; Wahyudin, Uyu; Sardin; Shantini, Yanti; Hufad, Achmad; Saepudin, Asep (Jurnal SOLMA, 2024)
Background: Management of B3 waste from the household sector still faces many obstacles, including the lack of knowledge and community participation in managing household B3 waste. The research aims to determine household knowledge and attitudes in sorting household B3 waste. Method This study used a quasi-experimental pre-posttest group design without a control group. The intervention took the form of learning through assistance in sorting household B3 waste to 18 heads of families in RW 06, Pasirkaliki Village, North Cimahi. Data was collected using a questionnaire sheet, then the data was analysed using the dependent T-test. Result: Respondents' knowledge level before the intervention was categorised as poor at 66.7%, while after the intervention it increased to 66.7% to good and 22.2% to very good. Before the intervention, 66.7% of respondents did not agree with sorting household B3 waste; after the intervention, 66.7% agreed and 22.2% strongly agreed. Based on the analysis, a p-value of 0.002 <0.05 was obtained, meaning there was a significant difference between the respondents' knowledge before and after the intervention. Conclusion: Family learning through mentoring can increase family knowledge and attitudes in sorting household B3 waste.